Evaluation of retinal function improvement in neovascular age-related macular degeneration after intravitreal aflibercept injections with the use of the assessment of retinal sensitivity: The use of the assessment of retinal sensitivity in anti-VEGF treatment – a STROBE-compliant observational study - Michalska-Małecka, Katarzyna (Medicine (Baltimore), 2019)
This study compares 2 methods of macular function evaluation: the microperimetric examination (mean central retinal sensitivity and fixation stability) and the distance best-corrected visual acuity (BCVA) examination, which is the most frequently used method of assessing macular function in patients with newly diagnosed wet age-related macular degeneration (AMD) who have been treated with anti-vascular endothelial growth factor (VEGF) drug (aflibercept). Prospective analysis was conducted on 44 eyes of 44 patients treated with intravitreal injection of anti-VEGF (aflibercept) because of newly diagnosed neovascular AMD. According to the research protocol, all patients had a 6-month follow-up. The response to treatment was monitored functionallybyMP-1 microperimetry, fixation, and distance BCVA assessment after injection. Improvement of retinal sensitivity and BCVA was found under aflibercept treatment. There was statistically significant improvement in retinal sensitivity in the MP-1 study 3 and 6 months from the beginning of anti-VEGF therapy. Moreover, a significant improvement in retinal sensitivity between 3 and 6 months of observation was demonstrated. At the same time, up to 3 months from the beginning of treatment, BCVA improved significantly compared to the baseline value. In the 6th month of the study BCVA remained stable without further significant improvement. Microperimetric examination with medium sensitivity and fixation stability assessment is a very valuable test determining the retinal function. It is clear that examining the macular morphology itself in modern diagnostics is not enough to assess retinal function. Microperimetry technique is a valuable tool for functional long-term evaluation of retinal function (also for a period of more than 3 months).